Distributed memory parallel computing of three-dimensional variable-density groundwater flow and salt transport. (August 2021) - Verkaik, J.; van Engelen, J.; Huizer, S.; Bierkens, M.F.P.; Lin, H.X.; Oude Essink, G.H.P.
Highlights: SEAWAT is parallelized using a MPI distributed memory approach. Huge 3D SEAWAT models are now feasible for a wide range of users. For a hypothetical and a real-life test case we report speedups up to two orders. Abstract: Fresh groundwater reserves, being of vital importance for more than a billion of people living in the coastal zone, are being threatened by saltwater intrusion due to anthropogenic activities and climate change. High resolution three-dimensional (3D), variable-density (VD), groundwater flow and salt transport (FT) numerical models are increasingly being used to support water managers and decision makers in their strategic planning and measures for dealing with the problem of fresh water shortages. However, these computer models typically require long runtimes and large memory usage, making them impractical to use without parallelization. Here, we parallelize SEAWAT, and show that with our parallelization 3D-VD-FT modeling is now feasible for a wide range of hydrogeologists, since a) speedups of more than two orders of magnitude can be obtained as illustrated in this paper, and b) large 3D-VD-FT models are feasible with memory requirements far exceeding single machine memory.